Insights into Chemical Interactions and Related Toxicities of Deep Eutectic Solvents with Mammalian Cells Observed Using Synchrotron Macro–ATR–FTIR Microspectroscopy - Saffron J. Bryant; Zo L. Shaw; Louisa Z. Y. Huang; Aaron Elbourne; Amanda N. Abraham; Jitraporn Vongsvivut; Stephen A. Holt; Tamar L. Greaves; Gary Bryant (Biophysica, 2023)
Deep eutectic solvents (DESs) and ionic liquids (ILs) are highly tailorable solvents that have shown a lot of promise for a variety of applications including cryopreservation, drug delivery, and protein stabilisation. However, to date, there is very limited information on the detailed interactions of these solvents with mammalian cells. In this work, we studied six DESs and one IL that show promise as cryoprotective agents, applying synchrotron macro–ATR–FTIR to examine their effects on key biochemical components of HaCat mammalian cells. These data were paired with resazurin metabolic assays and neutron reflectivity experiments to correlate cellular interactions with cellular toxicity. Stark differences were observed even between solvents that shared similar components. In particular, it was found that solvents that are effective cryoprotective agents consistently showed interactions with cellular membranes, while high toxicity correlated with strong interactions of the DES/IL with nucleic acids and proteins. This work sheds new light on the interactions between novel solvents and cells that may underpin future biomedical applications.